USING PEER ASSISTED LEARNING STRATEGY TO IMPROVE READING COMPREHENSION OF ANALYTICAL EXPOSITION TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 11 PALEMBANG - Intan Permata Sari; Jenny Elvinna Manurung (Didascein : Journal of English Education, 2020)
The objective of this study was to find out whether or not there was any significant difference on reading comprehension of analytical exposition between the eleventh grade students’ of SMA Negeri 11 Palembang who were taught by using Peer Assisted Learning strategy (PALS) and those who were not and to find out whether or not it was effective to use Peer Assisted Learning Strategy (PALS) to improve reading comprehension of analytical exposition to the eleventh grade students’ at SMA Negeri 11 Palembang. This study used quasi experimental method to conduct the research. There were 78 students was taken as sample. Each class consisted 39 students from both XI IPS 3 as experimental group and XI IPS 4 as a control group. In collecting the data, the test was used in reading comprehension as a pretest and posttest. To verify the hypothesis, the result of independent sample t-test found that t-obtained (11.077) was higher than t-table (1.9917) with degree of freedom (df=76), and the significance 2-tailed was 0.000. The result of the data showed that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that there was any significant difference on reading comprehension between the eleventh grade students of SMA Negeri 11 Palembang who were taught by using Peer Assisted Learning Strategy (PALS) and those who were not and also it was effective to use Peer Assisted Learning Strategy (PALS) to improve reading comprehension of analytical exposition to the eleventh grade students of SMA Negeri 11 Palembang.Keywords: Reading comprehension, Analytical exposition, Peer Assisted Learning Strategy.